Proteômica de células ASK-2 (Atlantic Salmon Kidney 2) infectadas pelo vírus da anemia infecciosa do salmão - Denilson Eduardo Silva Cunha (2019)
Infectious salmon anemia (ISA) is a disease of farmed Atlantic salmon caused by the aquatic orthomyxovirus infectious salmon anemia virus (ISAV). Although several molecular studies have aimed to understand salmon-ISAV interaction, none of them has focused their attention upon the viral and host cell proteomes dynamics. We studied the dynamics of the proteome and ultrastructural changes of Atlantic salmon kidney (ASK-2) cells infected with ISAV up to 12, 36, 60 and 84 hours post infection by mass spectrometry based quantitative proteomics and transmission electron microscopy. A total of 1.726 proteins were identified. From these, 390 proteins were differentially expressed in relation of control group and 434 were identified exclusively in ISAV-infected cell cultures. Our data revealed that changes in salmon protein expression levels increase during viral infection, where, most proteins were significantly down-regulated. Bioinformatics analysis showed that differentially expressed proteins are involved in several biological processes, such as gene expression and immune response, suggesting that intracellular activities were changed upon viral infection. Through literature review, many of the proteins identified here have already been studied as host factors relevant for viral replication, acting from the entrance of the virus in the cell until its budding, especially for influenza virus. Our findings by electron microscopy confirmed some changes described in previous studies and also brought new changes in the cell. For the first time we are able to describe changes of the cellular proteome of the ASK-2 cells overtime, revealing dynamic regulation processes and provides evidence that ISAV infection has impact on the cell status at protein level.